Acute Kidney Injury because of Implanted Tobramycin Pellets: A Case Report. Issue 2 (6th April 2023) - Windfeld-Mathiasen, Josefine; Horwitz, Henrik; Schwartz, Frederik
Abstract : Case: A 50-year-old healthy man with normal kidney function underwent surgery for fracture-related infection. Unfortunately, the patient received 2.5 times the intended dose of tobramycin pellets in the medullary cavity and developed acute kidney failure. Given the intraosseous administration of tobramycin, the drug displayed an absorption-dependent pharmacokinetics and multiple treatments with hemodialysis were needed. However, the patient had a complete recovery, and the kidney function remained normal at the 2-year follow-up. Conclusion: Tobramycin pellets are nephrotoxic in supratherapeutic doses; however, it was reversible in this case. Owing to the intraosseous administration, multiple treatments with hemodialysis were required.